EFEK MICROWAVE PADA PADUAN SILIKA (SiO2) DARI SEKAM PADI DAN ALPHA ALUMINA (-Al2O3) - I Nyoman Sudiana; Muhammad Zamrun Firihu; La Aba; Lina Lestari; Prima Endang Susilowati (Jurnal Aplikasi Fisika, 2017)
Research on the effects of microwave on the composite of silica (SiO2) from rice husk and alpha alumina (α-Al2O3) had been conducted. This study aims to determine the effect of microwave on the density and pore volume percent of silica alumina ceramic. Alpha alumina powder silica powder was mixed with a variation of 75%:25%, 85%:15% and 95%:5%, then added  with PVA as gluten as much as 3% wt. Each sample was compacted with a pressure of 4 tons and sintering with temperature variations of 900, 1000 and 1100 oC. The results of characterization using microwave sintering was better than using a sintering furnace. Shown by the increase in density and decrease in percent pore volume faster in the microwave was at a ratio of 85%:15% and temperatures 1100oC microwave sintering has the density of 3.241 g /cm3 and a percent pore volume of 9.892% while the sintering furnace has a density value of 3.013 g /cm3 and the pore volume and percent of 16.238%. Keywords : microwave sintering, alumina, silica, density, pore.